Developing Student Critical Thinking Ability by Using Problem Based Learning (PBL) - Tri Novita Irawati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2018)
The ability to crittical thinking skills can develop through the application of learning that gives students opportunities in developing critical thinking skills. One of them through the problems applied in learning Problem-based learning (PBL). This type of research is Classroom Action Research (CAR). This study aims to determine the learning process of PBL and the level of students' critical thinking ability to know the application of Problem-based learning (PBL) learning model. Based on the results of the analysis of the application of PBL runs well and smoothly. The presentation of students' critical thinking ability increases from cycle 1 to cycle 2 which provides basic explanation of 25% increase, kemambuan, basic skill building skills increased 25% and concluding ability increased by 8%.Keywords: Critical Thinking Skills, Problem Based Learning (PBL) Learning